Cryopreservation of Atlantic salmon Salmo salar sperm: effects on sperm physiology. Issue 3 (12th July 2016) - Figueroa, E.; Valdebenito, I.; Merino, O.; Ubilla, A.; Risopatrón, J.; Farias, J. G.
Abstract : The objective of this study was to determine the effect of freezing on the function in Atlantic salmon Salmo salar spermatozoa. The semen was frozen in Cortland's medium + 1.3M dimethyl sulphoxide + 0.3M glucose + 2% bovine serum albumin (final concentration) in a ratio of 1:3 (semen:cryoprotectant) as the treatment (T) and fresh semen as the control (F). Straws of 0·5 ml of sperm suspension were frozen in 4 cm of N2 L. They were thawed in a thermoregulated bath (40° C). After thawing, the percentage of spermatozoa with fragmented DNA [transferase dUTP (deoxyuridine triphosphate) nick‐end labelling (TUNEL)], plasma membrane integrity (SYBR‐14/PI) and mitochondrial membrane potential (ΔΨMMit, JC‐1) were evaluated by flow cytometry and motility was evaluated by optical microscope under stroboscopic light. The fertilization rates of the control and treatment semen were tested at a sperm density of 1·5 × 10 7 spermatozoa oocyte −1, by observation of the first cleavages after 16 h incubation at 10° C. In the cryopreserved semen (T), the mean ± s.d . DNA fragmentation was 4·8 ± 2·5%; plasma membrane integrity 75·2 ± 6·3%; mitochondrial membrane potential 51·7 ± 3·6%; motility 58·5 ± 5·3%; curved line velocity ( V CL ) 61·2 ± 17·4 µm s −1 ; average‐path velocity ( V AP ) 50·1 ± 17·3 µm s −1 ; straight‐line velocity ( V SL ) 59·1 ± 18·4 µm s −1 ; fertilization rate 81·6 ± 1·9%. There were significant differences in the plasma membrane integrity, mitochondrial membrane potential, motility, fertilization rate, VCL, VAP and VSL compared with the controls ( P  < 0·05). Also the mitochondrial membrane potential correlated with motility, fertilization rate, V CL and V SL ( r  = 0·75; r  = 0·59; r  = 0·77 and r  = 0·79, respectively; P  < 0·05); and the fertilization rate correlated with V CL and V SL ( r  = 0·59 and r  = 0·55, respectively).